Correlation of CALL score with disease progression in COVID-19 patients - Subramanya, Preetham Beguru; Khan, Naazim Javed; Mahendra, M.; Khan, Imran; Ravikumar, Nisha (International Journal of Research in Medical Sciences, 2022)
Background: Many prognostic models have been introduced to predict the disease progression in an individual with COVID-19, CALL score is one among them. The objective of the study was to evaluate the role of comorbidity, high age, low lymphocyte count, high lactate dehydrogenase (CALL) score in predicting disease progression and mortality in COVID 19 patients. Methods: Total 105 patients were divided into - stable group (CALL≤6) and progressive group (CALL>6), Chi- square test and ROC analysis is applied to predict the outcomes like oxygen requirement, ICU requirement (high flow nasal oxygen), invasive ventilation requirement, increase in respiratory rate ≥30 Cpm and death/recovery with CALL score in both the groups. Results: ROC analysis was done to predict outcome based on CALL score in both groups which showed sensitivity 100% (91.6% to 100%), specificity of 8.2% (2.7 to 18.1%), PPV – 44% (42.16 to 45.86%) and NPV – 100%. Conclusions: Using the CALL score model with cut off of 6 points, clinicians can predict the progression risk in terms of higher respiratory rate ≥30 cpm, oxygen requirement, requiring ICU, death/ recovery.